Existence of Customary Law through Comparative Education between Dayak Ngaju Customary Law and National Law - Putri Fransiska Purnama Pratiwi; Suprayitno Suprayitno; Triyani Triyani (Budapest International Research and Critics University, 2020)
Resolving acts of adultery as the consequence of woman seducing a married man that sometime may lead to out of wedlock pregnany will not be sufficient to only be pursued through national legal channels in the point of view of the Dayak Ngaju tribe. National law regulates sanctions for adulterers/spouse poachers but does not consider the interests of legitimate wives who become the victims. This study aimed to educate the Dayak Ngaju tribe to have better knowledge regarding the local customary law and as a refinement material for the National Criminal Law.The research method used in this study was empirical research method conducted through interviews with damang and mantir adat in Palangka Raya City. The Dayak Ngaju Customary Law has distinct classification of adulterers. Therefore, all forms of actions committed by women who seduce other women's husbands are prohibited in Ngaju Dayak Customary Law. This is reinforced by different customary sanctions in each classification.The National Law has regulated the regulation regarding of homewreckers (husband poachers) in the latest Criminal Code Bill but does not formally regulate psychological recovery for wives who are the victims of infidelity.